Brief Research Report: The Association Between Educational Experiences and Covid-19 Pandemic-Related Variables, and Mental Health Among Children and Adolescents - Ramirez, Saray; Aldunate, María Paz; Arriagada, Carolina; Bueno, Massiel; Cuevas, Florencia; González, Xaviera; Araya, Ricardo; Gaete, Jorge (Frontiers in Psychiatry, 2021)
Introduction: Mental health problems among children and adolescents are frequent. Today, the world is facing a pandemic with a novel coronavirus, which is related to the higher rates of mental problems reported worldwide. The objective of this study was to determine the impact of the Covid-19 related experiences, educational experiences, and family functioning on mental health and wellbeing among children and adolescents in Chile during the Pandemic and lockdown health measures. Methods: This is a cross-sectional analysis of the first wave of an ongoing longitudinal study among girls and boys of Pre-Kindergarten to 12th grade (4-18 years old) in Santiago, Chile. The sample consisted of 979 students from eight different schools. The method of data collection was online surveys administered to parents and adolescents. The dependent variables were mental health problems and wellbeing. Several independent variables were assessed (sociodemographic variables, Covid-19 related experiences, related educational experiences, and family functioning). A descriptive analysis and univariable and multivariable regression models were performed to study the association between variables. Results: Positive educational experiences, primarily academic self-concept, reduced the probability of mental health problems and increased wellbeing. Among covid-19 related variables, practicing meditation or praying reduced emotional problems, while having family or health problems increased emotional problems among adolescents. No clear association between Covid-19 related experiences variables among children was found. Conclusions: Our findings may help educational and public health authorities to plan future school preventive interventions to improve mental health and wellbeing in this population.